Frailty among inpatients with Schizophrenia: Status, influencing factors, and their correlation with quality of life - Yang, Cui; Hou, Xiaofeng; Ma, Xiucheng; Wu, Dongmei (Frontiers in Psychiatry, 2023)
Objective This study aimed to understand frailty and its influencing factors in inpatients with Schizophrenia in Chengdu and to explore correlations between frailty and quality of life. Methods From May to July 2022, inpatients with Schizophrenia were surveyed using a general information questionnaire, frailty phenotype (FP) scoring, the Self-Rating Depression Scale (SDS), the Mini-Mental State Examination (MMSE), and the SZ Quality of Life Scale (SQLS). Multivariate logistic regression was conducted to assess factors influencing frailty and multivariate linear regression was conducted to assess the factors influencing quality of life. Results A total of 556 hospitalized patients with Schizophrenia were included and divided into three groups according to the degree of frailty, of which 153 cases (27.5%) were without frailty, 348 cases (62.6%) were in early frailty, and 55 cases (9.9%) were in frailty. Univariate analysis of age, history of falls during hospitalization, polypharmacy, compulsory treatment during hospitalization, self-reported health status, activity level, cognitive impairment, depressive symptoms, “psychology and society,” “motivation and energy” and “symptoms and side-effects” showed statistically significant differences between the groups. Multinomial logistic regression showed that age, BMI, self-reported health, activity, cognitive impairment, motivation and energy, and symptoms and side-effects were influencing factors for frailty in hospitalized patients with Schizophrenia. Correlation analysis shows that frailty score positively correlated with SQLS score. Conclusion We found that frailty was prevalent and that frailty was positively correlated with SQLS scores in inpatients with Schizophrenia. To effectively manage the frailty of hospitalized patients with Schizophrenia, medical staff should pay attention to its influencing factors and quality of life.